Circulating monocyte subsets in human chronic graft-versus-host disease. (December 2018) - Konuma, Takaaki; Kohara, Chisato; Watanabe, Eri; Mizukami, Motoko; Nagai, Etsuko; Oiwa-Monna, Maki; Tanoue, Susumu; Isobe, Masamichi; Jimbo, Koji; Kato, Seiko; Takahashi, Satoshi; Tojo, Arinobu
Abstract Chronic graft-versus-host disease (cGVHD) is a major cause of late morbidity and mortality after allogeneic hematopoietic cell transplantation (HCT). Monocytes/macrophages play a central role in inflammation, tissue repair, and fibrosis, which are the main clinical features of cGVHD. Here, we examined the expression levels of activation markers, chemokine receptors, and scavenger receptors for each circulating monocyte subset in 145 patients without disease recurrence at least 12 months after undergoing allogeneic HCT. There were no significant differences in the numbers and the proportions of each monocyte subset between patients without cGVHD and those with mild or moderate/severe cGVHD. Lower expression of CCR5 on classical monocytes, and higher expression of CD204 and lower expression of CX3 CR1 on non-classical monocytes were associated with joint, and lung cGVHD, respectively. These data showed that alterations of activation markers and chemokine and scavenger receptors in each circulating monocyte subset were associated with the development of organ-specific cGVHD. Alterations of surface markers in each circulating monocyte subset may be candidate biomarkers for cGVHD.